Studying the Formation of Fullerenes During Catagenesis - Jens Dreschmann; Wolfgang Schrader (Molecules)
The formation of polycyclic aromatic hydrocarbons (PAHs) during catagenesis does not exclusively lead to planar structures. The inclusion of five-ring elements increases the curvature of PAHs and yields bent molecules. These bowl-like configurations may end in the formation of spherical carbon allotropes as fullerenes or nanotubes, as recently shown. The presence of fullerenes in crude oil raises the question of why the reaction is feasible under catagenic conditions although the laboratory synthesis of fullerenes commonly requires high-energy environments. This study focuses on the feasibility of the simulation of catagenesis under laboratory conditions and the question of which building blocks may lead to spherical structures. Possible educts, reaction mechanisms, and conditions such as temperature are discussed and related to experimental outcomes. For the simulation under laboratory conditions, a light gas condensate was fractionated by distillation in order to reduce the number of compounds per fraction and make them distinguishable. The characterization of the resulting fractions was performed through GC-MS and GC-FID measurements before heat application in a closed reactor. High-resolution mass spectrometry (HRMS) measurements of the products indicated PAH growth and, more importantly, the formation of fullerenes. Interestingly, the characterized fullerenes mostly comprised the range of non-IPR (isolated pentagon rule) fullerenes.